Education on the Impact Violence Against Children - Taufik, Iqbal; Muammar, Muammar; Labetubun, Muchtar Anshary Hamid; Irham, Muhammad; Baranyanan, Soeleman Djaiz (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Violence against children refers to any act that causes suffering and distress, whether physically, mentally, sexually, or psychologically, including actions that degrade the dignity of a child.Purposes of The Devotion: To raise awareness about the impact of violence against children at Sekolah Menengah Pertama Negeri 7 Ambon. Method of The Devotion: The method used in the implementation of assistance and educational activities on legal counseling regarding child legal protection at State Junior High School 7 Ambon.Results Main Findings of the Devotion: Socialization for the students of State Junior High School 7 Ambon: Through this community service activity, we have all learned that violence against children—whether physical, verbal, or emotional, can have very serious impacts on personal development, self-confidence, and the future of the child.